Impact of spacers and thermocycling on porosity and gaps in class II endodontic temporary restorations evaluated by microcomputed tomography - Fahda N. Algahtani; Manal Alkadi; Hiba R. Talic; Sarah S. AlShalawi; Lujain M. Alqarni; Reem M. Barakat; Rasha Haridy; Sara M. ElKhateeb; Rahaf A. Almohareb (Scientific Reports)
Abstract To use microcomputed tomography (micro-CT) to evaluate the porosity (%) of 3 M Pink Cavit (PC) and Riva Light Cure resin-reinforced glass ionomer (Riva RRGI) dental restoration when used over two types of spacers in Class II endodontically accessed premolars and investigate the effect of thermocycling on the porosity of the two biomaterials. Forty-four single-rooted human premolars were endodontically accessed, and a class II mesial box was prepared. Four experimental groups (n = 9) were defined based on the type of spacer and restoration used: PC and cotton pellet, PC and polytetrafluoroethylene (PTFE), Riva RRGI and cotton pellet, and Riva RRGI and PTFE. In two control groups (n = 4), PC or Riva RRGI was used alone. All the groups underwent thermocycling. The porosity was measured before and after thermocycling using micro-ct. The results were analyzed using t-tests and one-way ANOVA with significance set at P < 0.05. Both PC and Riva RRGI exhibited inherent porosity, with porosity increasing after thermocycling (P = 0.015 and P < 0.001, respectively). Cotton pellets increased the percentage of the gap between the restoration and dental walls with both restoration materials before and after thermocycling. Thermocycling increased the porosity of both PC and Riva RRGI restorations. In Class II endodontic access cavities, spacer choice influenced gap formation, with PTFE proving to be a better alternative to cotton pellets.